2022
DOI: 10.5588/ijtld.21.0676
|View full text |Cite
|
Sign up to set email alerts
|

Implementing 3HP vs. IPT as TB preventive treatment in Pakistan

Abstract: BACKGROUND: We assessed treatment uptake and completion for 6 months of isoniazid (6H) and 3 months of isoniazid plus rifapentine weekly (3HP) in a programmatic setting in Pakistan.METHODS: All household contacts were clinically evaluated to rule out TB disease. 6H was used for TB preventive treatment (TPT) from October 2016 to April 2017; from May to September 2017, 3HP was used for contacts aged ≥2 years. We compared clinical evaluation, TPT uptake and completion rates between contacts aged ≥2 years in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
6
2
Order By: Relevance
“…In this study, lack of willingness for TST screening among the contacts was primarily due to lack of symptoms related to TB disease, and the concern over opportunity and travel costs incurred in travel to the health facility for undergoing screening. These findings are consistent with a study in Pakistan [17]. Another prospective study in Peru observed that transport vouchers increased the acceptability of TPT among household contacts of TB cases signifying potential usefulness of similar interventions in contacts belonging to economically vulnerable categories in India [20].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In this study, lack of willingness for TST screening among the contacts was primarily due to lack of symptoms related to TB disease, and the concern over opportunity and travel costs incurred in travel to the health facility for undergoing screening. These findings are consistent with a study in Pakistan [17]. Another prospective study in Peru observed that transport vouchers increased the acceptability of TPT among household contacts of TB cases signifying potential usefulness of similar interventions in contacts belonging to economically vulnerable categories in India [20].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, nearly six in 10 TB household contacts were LTBI positive which is nearly double the prevalence in the general population [13], and also higher compared to the findings in a South Indian study (52.6%) [23]. Increasing age was the only sociodemographic factor which had significantly higher odds of LTBI positivity in the present study which is consistent with the previous evidence where association of sociodemographic factors was lacking except for sleeping on the same bed [17, 23]. These findings provide corroborative evidence and further programmatic justification to expand the coverage of TPT selectively among household TB cases in the road to TB elimination for high TB burden countries.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations